2009
DOI: 10.1161/strokeaha.108.524678
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History and Predictive Features of Hemorrhage From Brain Arteriovenous Malformations

Abstract: Background and Purpose-Patients harboring brain arteriovenous malformations (bAVMs) are at a lifelong risk for hemorrhagic strokes, but the natural history is poorly understood. We examined the impact of demographic and angiographic features on the likelihood of future hemorrhage. Methods-A prospectively accrued database of bAVM patients maintained at the Toronto Western Hospital was analyzed; 678 consecutive, prospectively enrolled bAVM patients were followed for 1931.7 patient-years. The rate of hemorrhage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
264
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(279 citation statements)
references
References 36 publications
4
264
5
1
Order By: Relevance
“…However, such patients represent a large portion of those with unruptured AVMs in the community, thereby compromising the generalisability of the study's findings. Furthermore, as the different AVM treatment modalities have progressed considerably during the last two decades [5,8,11,21,23], the threshold for proposing a prophylactic treatment of AVMs considered to harbour a high risk of rupture has been lowered, despite the results of different studies regarding the rupture risk factors [4,6,8,9,20]. Consequently, the patients included in ARUBA had possibly low-risk AVMs with a more favourable natural history.…”
Section: Critiquementioning
confidence: 99%
“…However, such patients represent a large portion of those with unruptured AVMs in the community, thereby compromising the generalisability of the study's findings. Furthermore, as the different AVM treatment modalities have progressed considerably during the last two decades [5,8,11,21,23], the threshold for proposing a prophylactic treatment of AVMs considered to harbour a high risk of rupture has been lowered, despite the results of different studies regarding the rupture risk factors [4,6,8,9,20]. Consequently, the patients included in ARUBA had possibly low-risk AVMs with a more favourable natural history.…”
Section: Critiquementioning
confidence: 99%
“…The cause of cerebral AVM is unknown, but AVM is usually congenital and forms during the third week of fetal development. Although the prevalence of cerebral AVM in humans cannot be precisely determined, AVM is uncommon and estimates vary from about 0.001% to 0.5% of the population [1,[9][10][11]. AVM is frequently asymptomatic and therefore remains undiagnosed [4], but AVMs can cause severe and devastating effects when they bleed.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and at least one single-center analysis have suggested that pregnancy increases the risk for hemorrhagic stroke, which can be partly explained by an increased tendency for cerebral AVMs to rupture during pregnancy [9]. It has been reported that pregnant women may have a four times greater risk of AVM rupture than non-pregnant women [7].…”
Section: Discussionmentioning
confidence: 99%
“…tion of Glubran 2, though the injection time is short. The majority of our patients were ruptured AVMs, so aggressive treatment to prevent recurrent hemorrhage was reasonable, considering the relatively higher rebleeding rate for AVM patients with hemorrhage presentation [9][10][11] . Several factors such as the angioarchitecture of the AVM, blood flow rate, and operator experience could affect the final results.…”
Section: Fundingmentioning
confidence: 99%